The internal auditors’ responses in environmental auditing practices: problem solvers vs checker - Mohd Jamil, Muthyaah; Zainal Abidin, Nor Hafizah; Mohd Alwi, Norhayati (Virtus Interpress, 2023)
This study explored how internal auditors responded to environmental auditing practices (EAP). The study used interpretative research focused on multiple case studies: two Malaysian Local Governments (MLG) with single-case design and environmental auditing. This study utilized 25 interview sessions comprising the internal auditors, executives from audited departments and the Councillor of the Malaysian Local Governments. This study used the framework from Mantere (2008) and Taminiau and Heusinkveld (2017) as guidance during thematic analysis using Atlasti software to conclude. This study concluded that the internal auditors perform six enabler conditions in EAP. This study showed no evidence that the internal auditors performed narration and inclusion during the EAP. The prominent enabler condition was constructing trust by the internal auditors. This study indicated one new enabler condition, selective reporting from the findings. The new enabler helped the internal auditors to expand their role from checkers to problem solvers in EAP.